Novel water-based automated endoscope cleaning process vs conventional manual cleaning for reducing duodenoscope contamination - van der Ploeg, Koen; Severin, Juliëtte A.; Vos, Margreet C.; Erler, Nicole S; Bulkmans, Adriana J.C.; Bruno, Marco; Mason-Slingerland, Bibi C.G.C. (Endoscopy International Open, 2025)
Duodenoscope contamination remains a persistent problem, exposing patients to infection risks. Automation in reprocessing may limit human error, reduce workload, and increase uniformity and traceability. However, its effectiveness should be evaluated before implementation. This study assessed the impact of implementing a novel water-based automated endoscope cleaning process on duodenoscope contamination.This before-and-after intervention study compared duodenoscope cleaning methods. From January 2022 to December 2023, conventional manual cleaning was used. From January 2024 to June 2024, the AquaTYPHOON system (AT) replaced manual cleaning. Cultures from Pentax ED34-i10T2 patient-ready duodenoscopes were collected. The main outcome was the contamination rate with microorganisms of gut or oral origin (MGO). Secondary outcomes included contamination with solely gut bacteria. Non-inferiority of the AT was tested using a generalized estimating equation with a non-inferiority margin of 5%.During the manual cleaning period, 333 duodenoscope cultures of eight duodenoscopes were collected; during the AT period, 100 cultures were collected. Pre-introduction of the AT, the contamination rate with MGO was 21.6%, which fell to 16% post-introduction (risk difference: –5.6%, upper bound 90% confidence interval [CI] 6.8%). For gut bacteria, the contamination rate decreased from 14.4% to 9% (risk difference: –5.4%, upper bound 90% CI 3.9%), indicating non-inferiority.AT reduced the contamination rate with MGO, but non-inferiority was not demonstrated. For gut bacteria, AT was non-inferior to manual cleaning. These results are promising. However, future studies should confirm these findings in larger samples and explore other advantages of using the AT in duodenoscope cleaning.
Keywords: Pancreatobiliary (ERCP/PTCD); ERC topics; Quality and logistical aspects; Quality management; Hygiene